Odpowiedzi

2010-03-17T19:31:50+01:00
A) 5x+2x-7-9x+3x-8+20-8x=
=-7x+5
b)-5x-2y+4x-7x+8y-x+2-6y=
=-9x+2
c)-9z-4+3z-8y+7z-8y-2y-7=
=z-18y-11
1 4 1
Najlepsza Odpowiedź!
2010-03-17T19:32:42+01:00
A)5x+(2x-7)-9x-(-3x+8)+20-8x=5x+2x-7-9x+3x-8+20-8x=-7x+5
b)-5x+(-2y+4x)-(7x-8y)-x+(2-6y)=-5x-2y+4x-7x+8y=-9x+2
c)-9z-(4-3z)-8y-(-7z+8y)+(-2y-7)=-9z-4+3z-8y+7z-8y-2y-7=z-11-18y
1 5 1
2010-03-17T19:38:05+01:00
A)5x+(2x-7) - 9x-(-3x+8) + 20 -8x=5x+2x-7-9x+3x+8=x+1
b) -5x+(2y+4x) -(7x-8y) -x+(2-6y)=-5x+2y+4x-7x-8y-x+2-6y=-9x-12y+2
c) -9z-(4-3z) - 8y-(-7z+8y)+(-2y-7)=-9z-4-3z-8y+7z+8y-2y-7=-5z-2y-11